Technological Ecosystems in Health Informatics: A Brief Review Article - Zhongmei WU; Xiuxiu ZHANG; Ying CHEN; Yan ZHANG (Tehran University of Medical Sciences, 2016)
Background: The existing models of information technology in health sciences have full scope of betterment and extension. The high demand pressures, public expectations, advanced platforms all collectively contribute towards hospital environment, which has to be kept in kind while designing of advanced technological ecosystem for information technology. Moreover, for the smooth conduct and operation of information system advanced management avenues are also essential in hospitals. It is the top priority of every hospital to deal with the essential needs of care for patients within the available resources of human and financial outputs. In these situations of high demand, the technological ecosystems in health informatics come in to play and prove its importance and role. The present review article would enlighten all these aspects of these ecosystems in hospital management and health care informatics. Methods: We searched the electronic database of MEDLINE, EMBASE, and PubMed for clinical controlled trials, pre-clinical studies reporting utilizaiono of ecosysyem advances in health information technology. Results: The primary outcome of eligible studies included confirmation of importance and role of advances ecosystems in health informatics. It was observed that technological ecosystems are the backbone of health informatics. Conclusion: Advancements in technological ecosystems are essential for proper functioning of health information system in clinical setting.   Keywords: Ecosystems, Health informatics, Hospital administration